Doppler ultrasound to assess the pharmacodynamic effects of splanchnic vasoactive compounds. Issue 4 (12th October 2021) - Marynissen, Heleen; Lodeweyckx, Thomas; Bielen, Didier; de Hoon, Jan
Abstract : Aims: In search of noninvasive biomarkers to assess the pharmacodynamic effects of portal pressure‐lowering drugs, the reproducibility of flow measurements in the superior mesenteric artery was evaluated using Doppler ultrasound. Methods: A reproducibility study was conducted in 15 healthy male volunteers (18–50 y). Eight ultrasound measurements were performed for each subject: 2 observers each conducted 2 measurements during 2 separate visits. The following flow parameters were captured: peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI), volume flow (VF) and vessel diameter. Reproducibility was assessed by the intraclass correlation coefficient. Results: Results are presented as intraclass correlation coefficient [95% confidence interval]. The flow parameters PSV, EDV, PI and VF correlated excellently within observer during visit 1 (0.888 [0.748–0.953], 0.910 [0.793–0.962], 0.844 [0.656–0.933] and 0.916 [0.857–0.951], respectively) and visit 2 (0.925 [0.829–0.968], 0.942 [0.863–0.976], 0.883 [0.719–0.954] and 0.915 [0.855–0.951], respectively). Measurements conducted during 2 separate visits by 1 observer correlated well to excellently for PSV, EDV, PI and VF (0.756 [0.552–0.875], 0.836 [0.694–0.916], 0.807 [0.631–0.904] and 0.839 [0.783–0.882], respectively). Measurements conducted by 2 distinct observers correlated well to excellently for PSV, EDV and VF during visit 1 (0.813 [0.584–0.922], 0.884 [0.597–0.945] and 0.786 [0.575–0.899], respectively) and visit 2 (0.779 [0.498–0.912], 0.861 [0.672–0.945], 0.810 [0.553–0.926], respectively). Vessel diameter measurements were poorly reproducible. Conclusion: Doppler ultrasound is a reproducible method for flow measurements in the superior mesenteric artery in a standardized group of healthy volunteers. Therefore, it is a promising technique to assess pharmacodynamic effects of splanchnic vasoactive compounds in early clinical drug development.